On the Same Page? How Asymmetric Buyer–Supplier Relationships Affect Opportunism and Performance - Villena, Verónica H.; Craighead, Christopher W. (Production and Operations Management, 2017)
Research on buyer–supplier relationships (BSRs) has often focused on only one side of the relationship and, thus, has tended to overlook asymmetries. Yet, a buyer (supplier) may often deal with a bigger supplier (buyer) or one that has higher levels of trust, respect, and reciprocity. Therefore, we examined how two types of asymmetries—size and relational capital—affect perceived opportunism and performance. We used dyadic data from 106 buyers and their matched suppliers gathered from a survey and an archival database. The results demonstrate that the degree and direction of both asymmetries affect the BSR. Our results also reveal that an imbalance of relational capital in a firm's favor may have the opposite effect from that intended. In other words, the firm's counterpart perceives more, rather than less, firm opportunism. The results also suggest that a buyer observes lower benefits in the presence of size asymmetry, whereas the supplier's perception of benefits is unaffected. Thus, our research represents a significant step forward in understanding BSRs and asymmetries by (i) bringing attention to two key asymmetries inherent in BSRs and (ii) showing that these asymmetries are not unidirectional in their influence on perceived opportunism and performance.